The Influence of Social Media Influences Generation Z's Preferences in the 2024 Election (Discourse Journal on Law and Society, 2025)
The main aim of this research is to dissect the influence of social media use on election preferences among Generation Z. By identifying patterns of interaction and exposure to political information through digital platforms, this research provides a sharper understanding of the role of social media in Generation Z. Z's political preferences in the environment. election in 2024. Therefore, it is hoped that this research will provide useful insights for politicians in designing effective and applicable political strategies to reach and understand Generation Z.